SUBYEKTIVITAS AUDITOR JUDGMENTS SEBAGAI BAGIAN DARI PROFESIONALISME - Hidayah, Ade Irma (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2014)
This paper attempts to provide a descriptive explanation of auditorâ€™s judgments as a part of audit process. By using information from research and her personal experiences, the author provide a different way to understand the nature of auditorâ€™ subjectivity. According to standards established by Institute of Certified Public Accountant, auditor is required to perform audit using his/her professional judgment. The word â€professional judgmentsâ€ appear in every chapter of this standard. Auditor â€™opinion is expected to be objective and free from personal auditorâ€™ subjectivity. Although, the â€judgmentâ€ is very closely related to ideas, calculation and even the result of contemplation. Behind the screen of judgment making could not be separated from the condition of auditor. There is no perfection objectivity in a judgment. Therefor, subjectivity in audit judgment are necessity. However, judgment based on knowledge, experience, morality, common sense and conscience is accountable judgment.